ANALISIS LITERATUR TENTANG PENINGKATAN KETERAMPILAN PUKULAN LOB BULU TANGKIS MELALUI PENERAPAN VARIASI LATIHAN BERPASANGAN PADA SISWA SEKOLAH MENENGAH ATAS - Muhammad Yan Ahady; Maman Supriatman Mendrofa; Jhoseb Tarigan; Felix Veuster Bakkara; Harnaldi Josua Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of paired training variations in improving badminton lob stroke skills among senior high school students. The method used in this research is a literature review by analyzing various scientific articles, journals, and research reports related to badminton learning and training methods. The results of the review indicate that paired training variations can improve students' technical mastery, accuracy, consistency, motivation, and learning participation in performing badminton lob strokes. In addition, paired training provides more opportunities for students to practice repeatedly, receive direct feedback, and develop cooperation during learning activities. Therefore, paired training variations can be considered an effective learning strategy to improve badminton lob stroke skills among senior high school students.